High food prices: The proposed policy actions - von Braun, Joachim (2008)
The food price crisis hits a world that has the most unequal distribution of income ever, and a world that has left the poorest behind. The proportion of the ultra-poor who have incomes of less than half a dollar a day has declined even more slowly than those poor with one dollar a day. Progress toward achieving the poverty and hunger Millennium Development Goal is compromised for some time to come. The complex causes of the food and agriculture crisis require an equally complex and comprehensive response. In view of the urgency of assisting people and countries in need, we at the International Food Policy Research Institute suggest two sets of policy actions: an emergency package of four actions to take immediately and a resilience package of four actions to phase in now but whose impacts may take time. Takentogether, both packages add up to the needed impact.